Leukemie by kinders - M.J. Hugo; A. Botha (AOSIS, 1979)
Leucaemia is a major cause of death in children between the ages of one and fourteen years. Only a team whose members work well together can care effectively for a child with leucaemia, and of the team the nurse is one of the most important members. In order to maintain her place in the team it is essential for the nurse to keep up to date with the latest developments in the treatment of this formerly fatal illness.